Human resource management: independent curriculum development to increase student learning enthusiasm in schools - Laila Nurul Wahidah; Syunu Trihantoyo; Nuphanudin (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
Purpose this study aims to analyze the strategic role of Human Resource Management (HRM) in the development of the Independent Curriculum (Kurikulum Merdeka) to increase student learning enthusiasm, with a case study in madrasas in Surabaya. Method This research uses a descriptive qualitative approach with a case study method. Data were collected through in-depth interviews with principals and teachers, observation of classroom activities, and documentation studies of developed teaching modules. Findings the results show that HRM practices focusing on continuous competency development and teacher autonomy are key to the successful implementation of the independent curriculum. Curricula developed contextually and through differentiation have been proven to increase active student engagement, reduce boredom, and enhance intrinsic learning motivation. Implications school management must transform from administrative patterns to instructional leadership that supports teacher creativity. Curriculum success is not determined by formal documents but by the readiness of HR in executing student-centered learning.